ISLAMIC EDUCATION METHOD IN IMPROVING THE RELIGIOUS LEARNING QUALITY IN MADRASAH IBTIDAIYAH - Muhammad Ikhlas Rosele; Mansir, Firman; Nurul Aisyah (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2024)
Abstract This research emphasizes the importance of methods in learning religion for students at the elementary school or madrasah ibtidaiyah level. Learning materials that are not understood by students begin with the wrong method used by the teacher, so a method that is right on target is needed. The purpose of this study is to explain the importance of Islamic Education methods in improving quality learning in madrasah ibtidaiyah. The method used in this research is qualitative with a literature study approach, so that when analyzing data through literature review analysis of primary data and secondary data. This research shows that effective Islamic education methods with various variants can improve the quality of religious learning because with the right method, media sophistication and teacher competence can deliver religious learning easily absorbed and understood by students in madrasah ibtidaiyah. Thus, Islamic education methods have distinctive characteristics and are different from other subjects.